Pengaruh Gaya Belajar dan Metode Pembelajaran terhadap Hasil Belajar Peserta Pelatihan Fungsional Peneliti - Naily Kamaliah; Alpha Fadila Juliana Rahman (Pusdiklat Tenaga Teknis Pendidikan dan Keagamaan, 2021)
[THE INFLUENCE OF LEARNING STYLES AND LEARNING METHODS ON LEARNING OUTCOMES OF RESEARCHER FUNCTIONAL TRAINING PARTICIPANTS] The influence of visual, auditory, and kinesthetic learning styles, and aspects of the diversity of trainees in an effort to find appropriate learning methods, on the subject of analysis and interpretation of research data. The purpose of this study was to obtain an overview of aspects related to improving the learning outcomes of trainees and the achievement of learning objectives in the analysis and interpretation of research data. The instrument in this study used a questionnaire that was distributed online through the google form application, one day before learning, to all participants of the Pelatihan Pembentukan Jabatan Fungsional Peneliti (PPJFP), and resulted in a questionnaire that was received back as many as 139 questionnaires. Based on the results of the study, data were obtained which were then analyzed using descriptive statistical analysis and inferential statistics with Two Way ANOVA. The results of the study show that: first, learning styles determine which learning methods are more attractive to participants; second, learning outcomes are influenced by differences in whether or not participants have received the previous material and third, there is no effect of different participants' learning styles on learning outcomes.